Ecosystems, poverty and sustainable development goals to 2030: Analysis and reflections based on indicators, Piura – Perú - Rijalba Palacios, Pablo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Relationships between poverty, ecosystems and SDG 2030 in Piura are analysed. It is argued that the deterioration of ecosystems due to indiscriminate use and little regulation accentuate poverty. Applying descriptive, correlational and systematization methodology, indicator matrices are constructed with information from the Ministry of the Environment (MINAM), the National Statistics Institute (INEI) and the Central Reserve Bank (BCRP). The policies of the National Agreement have not allowed satisfactory results since ecosystem deterioration and unfulfilled SDGs are observed. The evidence supports the hypothesis that sustainable development requires transformation processes from ecosystems to natural capital through effective policies, social vigilance, and government effort.